The Evaluation Research of Bachelor Degree in Business Administration Marketing Program (Revised 2013) Business Administration Faculty Huachiew Chalermprakiet University - เลิศจริยพร, สุเมษ (Business Administration and Management Journal Review, 2019)
The research of evaluation of bachelor Degree Program is the process to collect all important data from all major participants involving running and managing program in purpose of verification, improvement and lead to major curriculum and program revision. With reference to Huachiew Chalermprakiet University’s Bachelor Degree in Marketing Program (Revised 2013), the Marketing Program (Revised 2013) is 4-year program and presently in turn of major revision for students admission in education year 2018. To design the revised 2018 program effectively, the research proceed Census Technique by collecting data and the result of the personal data consequently was concluded from population of 5-major group which consists of 94 samples from 1th-4th year students, 23 samples of graduates in education year 2016, 14 samples from employers/coworkers of graduates, 7 samples of marketing instructors and 22 samples of graduates’ parents. Summary of the accumulative grade of the 1th-4th year students were as; 50 percent of the total students gained between 2.00-2.49, 38.9 percent of the total students in the range between 2.50-2.99 and 5.6 percent of the total students gained between 3.00-3.49 and 3.50-3.99 respectively. The information from the research came out through 4 aspects as following details; 1. Context aspect consists of two topics; 2.1 topic of objective of Marketing Program The success of the objective of the program arrives from the program fulfills the students with knowledge comprehension both marketing and other concerned theories adapted in changing situation and environment at the top rank, nonetheless, the students still had weakness in English communication, capability of new technology devices. Implementing knowledge to the real working operation, and assisted students gained marketing career experiences. 2.2. structure and contents of Marketing program The information suggests the opinion pertaining structure and contents of Marketing program were optimum for total studying credits not less than 135 credits identified as 30 credits for general education course, 48 credits for business core course, 36 credits of major requirements, 9 major elective credits for Co-Operative Education course and 12 major elective for field work practice course. The outcomes of the research suggested that subject of GE 1113 Chinese Studies and IB 1013 ASEAN-Chinese Business should be removed from the program, meanwhile, EC 1003 Macroeconomics, FN 1603 Business Finance and BA4113 Taxation in business core course and MK 3613 Purchasing and Procurement, MK4693 Hospitality and Service Marketing, MK 3553 Integrated Marketing Communication, MK 3603 Sales Management and Sales Technique and MK3643 Field Work Pratices should have instruction modification. 2. Input aspect This aspect includes two significant aspects; students and infrastructures. Regarding student aspect, the information expresses the top rank schools which the 1th- 4th year students finished from comprising with Ratchadumri school and Nawamintrachinuthid Suankularpwittayalai Samutprakarn school, the second rank came from Samutprakarn school and Sirirattanathorn school. The reasons of studying the Marketing Program (Revised 2013) from the most choice was interest in Marketing Program, next choice was convenience of traveling and University close to accommodation and 3rd reason came from parents’ suggestion. According to the second aspect, studying infrastructure, the research recommended improvements by increasing number of computer set in computer laboratory, enhancing speed of WI-FI, modernizing marketing textbook in library consistent with the marketing subjects both Thai and English version. 3. Process aspect The research forms the results of the positive performance aspects of the Marketing program were convenience for student getting effective consulting and advice from adviser, having efficient marketing course management process, nevertheless, too little healthy and sport activities for students. 4. Product aspect The research suggests that graduates were employed in marketing field consists of Retailing, Wholesaling, Sales promotion, Purchasing, and Customer information career. Noticeably, the employers expected capabilities from the graduates comprising with Communication with influential persons with marketing technical term efficiently, ability of English communication and knowledge adaptation to real marketing operation.